Applying the complementary knowledge bases of System Dynamics and Indigenous knowledge in public health research in Aotearoa, New Zealand. (December 2022) - McKelvie-Sebileau, Pippa; Pekepo, Crystal; Rees, David; Swinburn, Boyd; Gerritsen, Sarah; Tipene-Leach, David
Systems Thinking is increasingly applied to address complex societal and public health issues in Aotearoa, New Zealand and has been proposed as a good fit with traditional wisdom and Mātauranga Māori (Indigenous knowledge) from Aotearoa, New Zealand. In this article, we delve into the theoretical underpinnings of Systems Thinking approaches used in Community-Based System Dynamics research and find parallels with Indigenous narratives and knowledge. The synergy created by combining these two knowledge systems and practices is proposed as an effective way to approach public health issues that emerge from complex adaptive systems, particularly in communities with large numbers of Indigenous peoples. Examples are given from an initiative to engage community to improve food security and nutrition in regional Aotearoa, New Zealand.